Iatrogenic tibial arteriovenous fistula after Fogarty balloon catheter graft thrombectomy. Issue 11 (9th November 2021) - Papadoulas, Spyros; Moulakakis, Konstantinos; Kouri, Natasa; Mulita, Francesk; Tsimpoukis, Andreas; Seretis, Charalampos; Kitrou, Panagiotis; Katsanos, Konstantinos; Kakkos, Stavros K.
Abstract: A 75‐year‐old male presented with an immediately threatened grade IIb acute ischemia of the left leg due to thrombosis of a femoro‐infrapopliteal prosthetic bypass graft. After an urgent Computed Tomography Angiography, an urgent graft thrombectomy was performed using a 5 Fr Fogarty catheter, which had a troublesome distal passage, causing a tibial A‐V fistula. Abstract : A hand‐held doppler device reaveals a continuous machinery bruit due to a tibial A‐V fistula